133k views
4 votes
Solve each quadratic equation. a^2 + 2a - 3 = 0

User Debaditya
by
6.0k points

2 Answers

1 vote

Answer:

a=1,-3

Explanation:

You would use the quadratic formula to get A and then if you wanted to check yourself you could plug back in and see if it equals 0

1^2+2(1)-3=0

(-3)^2+2(-3)-3=0

They are both true and both equals 0 so your answers would be a= 1,-3

Hope this is Helpful

User Shiridish
by
5.1k points
4 votes

Answer:

y=(a+2)(a-1)

Explanation:

sum - +2

product - -3

factors - +2, -1

y=(a+2)(a-1)

x intercepts will be -2, +1

User Petermeissner
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.